Exchange rates and international finance - Copeland, Laurence S. (Harlow, England ; New York : Financial Times Prentice Hall, 2005)
This title provides a clear and concise guide to the essentials of exchange rate theory and its relevance to major events in currency markets.
Includes bibliographical references and index.
oif 01/09/15
Loan
Keywords: Foreign exchange rates; International finance